A joint resource allocation scheme for OFDMA–based wireless pervasive networks with carrier aggregation. (30th May 2013) - Wu, Fan; Leng, Supeng; Mao, Yuming; Huang, Xiaoyan
The mixture of users with different capabilities of Carrier Aggregation (CA) presents new challenges to optimise the performance of the next generation wireless pervasive networks. This paper focuses on the joint resources allocation for OFDMA–based multi–carrier system, with the objective of maximising the network utility. Distinguished from many existing methods, our approach combines dynamic spectrum resources assignment and adaptive power allocation technologies for the CA networks. We propose a novel scheme with Joint Component Carrier (CC), Resource Block (RB) and Power Allocation (JCRPA), where the Minimising System Utility Loss (MSUL) algorithm is developed to allocate both CCs and RBs for different users with various CA capabilities. Furthermore, with the cooperation of the JCRPA scheme, a CC–switch control mechanism is devised to reduce the overhead due to frequent CC switching. Simulation results demonstrate that JCRPA is able to significantly improve the system performance in terms of network utility, average throughput and transmission fairness.